DNA persistence after treatment of Lyme borreliosis - Pícha, D; Moravcová, L; Vaňousová, D; Hercogová, J; Blechová, Z (Folia microbiologica, 2014)
One hundred twenty-four patients-53 with neuroborreliosis, 48 with erythema migrans, and 23 with Lyme arthritis-were tested in a prospective study for the presence of the DNA of Borrelia burgdorferi sensu lato in plasma, cerebrospinal fluid (CSF), urine, and synovial fluid by nested polymerase chain reaction (PCR). Specific DNA was detected using five amplification systems simultaneously: three targeted chromosomal genes encoding 16S rDNA, flagellin, and p66; and two plasmid sequences of OspA and OspC. Patients were examined clinically and by PCR before and after treatment and again after 3 and 6 months. Before treatment, the specific DNA was detected in 78 patients (62.9 %). Forty-one neuroborreliosis patients were DNA-positive (77.4 %), with CSF positivity in 26 patients, urine in 25, and plasma in 16. Twenty-six erythema migrans patients were DNA-positive (54.2 %), with plasma positivity in 18 cases and urine in 14. Eleven Lyme arthritis cases (47.8 %) were DNA positive (six in urine, five in plasma, and four in synovial fluid). The frequency of PCR positives was comparable in CSF and urine, and it was lower by approximately 50 % in plasma. Specific DNA was also found in a significant number of patients in later testing periods: 48 patients after treatment, 29 patients after 3 months, and 6 patients after 6 months. The prolonged PCR positivity was not explainable by persistent infection according to the clinical manifestations of the disease. Possible explanations of the problem are discussed.
Keywords: časové faktory; tělesné tekutiny; Time Factors; Body Fluids; Borrelia burgdorferi komplex; Polymerase Chain Reaction; lymeská nemoc; polymerázová řetězová reakce; DNA, Bacterial; DNA bakterií; lidé; Humans; Borrelia burgdorferi Group; Lyme Disease